The image of crucified Christ in the art of cláudio pastro: an investigation based on the artist's personal collection - Souto, Hilda [UNESP]; Fernandes, Márcio Luiz (Universidad Pontificia Bolivariana, 2023)
The object of study in this article is the figure of Christ naked on the cross, a graphite pencil drawing that is part of the paper collection of the visual artist Cláudio Pastro (1948-2016), under the custody of the Monastery of Nossa Senhora da Paz. The main objective is to analyze this image with aesthetic and theological criteria, addressing unprecedented aspects not presented in the public work, deepening a reflection on who Jesus is in Pastro's work. The methodology used is Genetic Criticism, which focuses on the creative process. The method suggests a permanent dialogue between the originals (sketches, studies, notes, etc.) and the final work. The drawing was analyzed with reference to authors from the fields of visual arts, theology, and the History of Sacred Art, indicating the necessary developments that occurred in the representation of the crucified Christ in different historical periods. In the specific case of Pastro, his essential features in representing Christ naked on the cross depict the kenosis of God, who, humbling himself to human condition and becoming flesh, became man without ceasing to be God.
A IMAGEM DO CRISTO CRUCIFICADO NA ARTE DE CLÁUDIO PASTRO: UMA INVESTIGAÇÃO A PARTIR DO ACERVO PESSOAL DO ARTISTA
La imagen de cristo crucificado en el arte de Cláudio Pastro: una investigación a partir de la colección personal del artista
Keywords: Cláudio Pastro; Collection; Creative Process; Cross; Crucifixion; Genetic Criticism; Religious Art; Theology; Vatican Council II; Visual Arts